WAYS OF FORMATION OF CITIES IN THE ZARAFSHAN OASIS - Abdirakhmonova Mahfuza Nodir qizi; Rustamova Laylo O’ralovna (Bright Mind Publishing, 2025)
This article discusses the formation of the historical cities of the Zarafshan oasis and the emergence and development of community centers in this process.
Keywords: Zarafshan River, Lake Mokhandarya, Kaltaminor, Bactria, Sogdiana, Khorezm, Parkana, Burgut Castle in Khorezm, Dargam Canal in Samarkand.